Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi Dan Pelatihan Penyusunan Laporan Keuangan Terhadap Pelaporan Keuangan Bumdes Berdasarkan SAK ETAP - Sahrul HI Posi; Sang Putu Angga Mahendra Putra (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
The purpose of this study aims to determine the factors that affect the financial reporting of BUMDes based on SAK ETAP. This research method uses quantitative descriptive methods and primary data. This study took a sample of 47 BUMDes in 5 districts in North Halmahera Regency. The sampling technique used in this study was purposive sampling technique.The results showed that the level of education had no effect on the financial reporting of BUMDes based on SAK ETAP. Accounting understanding has a positive effect on BUMDes financial reporting based on SAK ETAP. Financial report preparation training has no effect on BUMDes financial reporting based on SAK ETAP. This research specifically explains how the level of education, understanding of accounting, and training in the preparation of BUMDes financial statements in North Halmahera Regency is influenced, so that it can be used as a guide for the government to make policies related to BUMDes financial management in accordance with applicable regulations. This research is only limited to 47 BUMDes in 5 Districts. So it is suggested to further researchers to expand the object of research but to add other objects such as in every sub-district in North Halmahera Regency